Role of Social Media Optimization in Digital Marketing with special reference to Trupay - Sahai, Seema; Goel, Richa; Malik, Priyanka; Krishnan, Chitra; Singh, Gurinder; Bajpai, Chitra (International Journal of Engineering and Technology, 2018)
Social media optimization has been used by many organizations in the recent years, after the growth of Internet, for enhancing the growth and profits of their business. This paper discusses some of the strategies of digital marketing adopted by Trupay after the period of demonetization in India.SMO (Social Media Optimization) can be defined as the process of increasing the popularity and awareness of the product in the minds of the people. It is basically a marketing tool which helps in the promotion, marketing and sale of the product. Digital marketing is the method of promoting a product or a brand using electronic media like Mobile marketing, E-mail marketing etc..Â Â